Energetic feedings influence beeswax production by Apis mellifera L. honeybees - Carrillo, Marcela Pedraza [UNESP]; Kadri, Samir Moura [UNESP]; Veiga, Nabor [UNESP]; Orsi, Ricardo Oliveira [UNESP] (Universidade Estadual de Maringa, 2015)
The effect of different types of energy feeding (sugar syrup, inverted sugar and juice of sugar-cane) on beeswax production and its economic feasibility are evaluated. Twenty beehives of Africanized Apis mellifera were selected, and five were used for each type of feeding. The treatments were T1 (sugar-cane juice), T2 (sugar syrup) and T3 (inverted sugar). Feedings was provided by Boardman feeders and the amount was adjusted according to consumption. A layer of beeswax was manually set up into the honeybee nest and beeswax built area was measured weekly. Total reducing sugar, calorimetry, dry matter and ashes of all feedings were analyzed. Data were analyzed by analysis of variance with Tukey's test to determine differences among averages. The average consumption of inverted sugar was significantly lower than that of other treatments. The highest beeswax production average occurred in the sugar syrup treatment. The highest average of ashes, dry matter and reducing sugar occurred, respectively, in sugar-cane juice, inverted sugar and sugar syrup. Sugar syrup may be an alternative energy source for beeswax production, although sugar-cane juice may be more profitable.

Os objetivos do presente trabalho foram avaliar a interferência de alimentos energéticos na produção de cera e sua viabilidade econômica. Foram selecionadas 20 colmeias de abelhas Apis mellifera africanizadas, cinco por tratamentos, sendo: T1: Garapa; T2: Xarope de açúcar e T3: Açúcar invertido. Os alimentos foram fornecidos por meio de alimentador tipo Boardman e a quantidade ajustada em função do consumo. A produção de cera foi analisada semanalmente. Foram analisados os açúcares redutores totais, a calorimétrica, a matéria seca e as cinzas. Para a análise dos dados foi utilizada a Análise de Variância seguida do teste de Tukey. O consumo médio de açúcar invertido foi significativamente menor em relação aos outros tratamentos. A maior produção média de cera ocorreu no T2. O maior valor de açúcar redutor e calorimetria foram encontrados no T2, em comparação com os demais tratamentos. Por outro lado, o T2 apresentou o menor valor de cinzas. Para matéria seca, o maior valor foi encontrado em T3. Com relação à análise econômica, esta tornou-se mais viável como uso da garapa de cana-de-açúcar. Pode-se concluir que o xarope de açúcar pode ser uma alternativa para induzir a produção de cera em abelhas Apis mellifera embora a garapa seja economicamente mais viável.
Alimentação energética influencia produção de cera por abelhas Apis mellifera L.
Keywords: Beekeeping; Economic viability; Feed; Honeybee; Apicultura; Viabilidade econômica; Alimentação; Abelhas